Proporsi gangguan tidur pada mahasiswa program studi pendidikan dokter semester satu dan semester tujuh Fakultas Kedokteran Universitas Udayana, Bali, Indonesia - I Nyoman Andika Kumara; Luh Nyoman Alit Aryani; Ni Ketut Sri Diniari (DiscoverSys Inc., 2019)
Background: Higher education changes status from student into college-student. In Indonesia, it is regarded more than just student, which make college student have more higher demands. Academic demands they face become their stressor. And this stressor itself can trigger sleep disturbance, especially in medical students.Objective: This research was aimed to determine the proportion of sleep disturbance among medical students in the first and seventh semester at the Medical Faculty of Udayana University.Methods: A cross-sectional descriptive study was conducted to know the proportion of sleep disturbance among medical students in first and seventh semester at Medical Faculty of Udayana University, as much as 140 college students used as samples and chosen by stratified random sampling method and using Pittsburgh Sleep Quality Index (PSQI) as an instrument for sleep disturbance measurement. Data were analyzed using SPSS version 17 for Windows.Results: The results of the study found that 81 students experience sleep disturbance, and found more in student in the first semester at about 33,5% than in seventh semester student which only approximately 24,2 %. Other results based on ages and sex concluded students with the age of 18 experience sleep disturbance the most and dominantly by female students.Conclusion: Most first semester students experience sleep disorders where the highest rate is at the age of 18 years and female sex